Chalinulasterol, a Chlorinated Steroid Disulfate from the Caribbean Sponge Chalinula molitba. Evaluation of Its Role as PXR Receptor Modulator - Teta, Roberta (MDPI, 2012)
Chalinulasterol (1) a new chlorinated sterol disulfate was isolated from the Caribbean sponge Chalinula molitba. Its structure was elucidated using mass spectrometry and NMR experiments. The possible role of chalinulasterol as modulator of the PXR nuclear receptor was investigated but, in spite of the close structural relationship with the PXR agonist solomonsterol A (2), it showed no activity. The structural requirements for the PXR nuclear receptor activity were discussed.